A Case Study of Change in the Teaching and Learning of Precalculus to Calculus 2: What We are Doing With What We Have. Issue 6 (3rd July 2018) - Apkarian, Naneh; Bowers, Janet; O'Sullivan, Michael E.; Rasmussen, Chris
Abstract: This article presents a case study that details the successes and lessons learned by faculty and administrators at San Diego State University (SDSU) who are in the process of implementing a substantial improvement to the Precalculus to Calculus 2 sequence. Improvement efforts have been informed by national studies of successful programs and center on the department as the primary agent of change. The majority of the article will discuss the particular changes that are being enacted at SDSU, with special attention to how they came to be as they are, how they are being implemented, and how we have identified and addressed salient concerns during the process. We conclude with how we intend to continue and expand our efforts to improve student success in introductory mathematics courses and a discussion of the lessons we have learned along the way.